Comparative Effectiveness of nab-Paclitaxel Plus Gemcitabine vs FOLFIRINOX in Metastatic Pancreatic Cancer: A Retrospective Nationwide Chart Review in the United States - Sunnie Kim; James Signorovitch; Hongbo Yang; Oscar Patterson‐Lomba; Cheryl Xiang; Brian Ung; Monika Parisi; John L. Marshall (2018)
nab-Paclitaxel plus gemcitabine (nab-P + G) and FOLFIRINOX (FFX) are among the most common first-line (1L) therapies for metastatic adenocarcinoma of the pancreas (MPAC), but real-world data on their comparative effectiveness are limited.